A METHOD FOR CALIBRATING 10-TURN AND 50-TURN CURRENT COIL USING MULTIPRODUCT CALIBRATOR - Hayati Amalia; Agah Faisal (JURNAL STANDARDISASI, 2019)
This paper presents a traceable measurement method developed in the Laboratory of National Measurement Standards for Electricity and Time (NMS Lab for Electricity and Time) - National Standardization Agency of Indonesia for calibrating current coil in order to obtain correction and uncertainty estimation of the current coil windings number (N). Current coils as objects of this research were 10-turn and 50-turn current coil. Calibration was performed using standard multiproduct calibrator (MPC) and two auxiliary devices, current coil F-5500 and clamp meter F-337. Correction and uncertainty values of N current coil were evaluated for DC and AC supplied current using formulation developed based on principle of current division between current coil output and supplied current from MPC. Based on evaluation result analysis, the expanded uncertainties of this method span from 0.47% to 1.0% (when supplied by DC current) and from 0.57% to 1.1% (when supplied by AC current) for 10-turn current coil, and span from 0.44% to 0.65% (when supplied by DC current) and from 0.54% to 0.96% (when supplied by AC current) for 50-turn current coil. Moreover, it also showed that the largest uncertainty component came from current coil F-5500. Meanwhile, the largest correction for 10-turn current coil was obtained 1.2% at 10 A DC, and for 50-turn current coil was obtained -0.47% at 700 A AC. Verification of the calibration and evaluation methods had also been carried out and it indicated that the calibration and analysis methods developed can be used to examine the performance of the current coil.